Ultrahigh Sensitive Detection of Tau Protein as Alzheimer's Biomarker via Microfluidics and Nanofunctionalized Optical Fiber Sensors - Chiavaioli, Francesco; Santano Rivero, Desiree; Del Villar, Ignacio; Socorro‐Leránoz, Abián B.; Zhang, Xuejun; Li, Kaiwei; Santamaría, Enrique; Fernández-Irigoyen, Joaquín; Baldini, Francesco; van den Hove, Daniel L. A.; Shi, Lei; Bi, Wei; et al. (Advanced photonics research, 2022)
Alzheimer's disease (AD) is one of the most common neurodegenerative illnesses displaying the highest death rate in the elderly. However, the existing AD diagnostic system remains elusive due to lack of a technology that may ensure enough sensitivity and reproducibility, detection accuracy, and specificity. Herein, a straightforward approach is reported to realize lab‐on‐fiber (LoF) technology for AD biomarker detection based on a D‐shaped single‐mode fiber combined with nanometer‐scale metal‐oxide film. The proposed sensing system, which permits the generation of lossy‐mode resonance (LMR), remarkably increases the evanescent field of light guided through the fiber, and hence the fiber‐surrounding medium interaction. Moreover, such optical sensors are highly repeatable in results and can safely be embedded into a compact and stable microfluidic system. Herein, the specific detection of Tau protein (as one of the classical AD biomarkers that is highly correlated with AD progression) in a complex biofluid with a detection limit of 10−12 m and over a wide concentration range (10−3–10 μg mL−1) is successfully demonstrated. The proposed LoF biosensor is an appealing solution for rapid, sub‐microliter dose and highly sensitive detection of analytes at low concentrations, hereby having the potential toward early screening and personalized medicine in AD. The combination of microfluidics and nanofunctionalized optical fiber sensors is an appealing solution for rapid, sub‐microliter dose and highly sensitive detection of analytes at low concentrations, hereby having potential in early screening and personalized medicine. The specific detection of Tau protein (highly correlated with Alzheimer's disease progression) in complex biofluid with detection limit of 10−12 m is successfully demonstrated.